Pengembangan Proyek Mini Automasi Workflow Berbasis N8N Untuk Mendukung Inovasi Digital Masyarakat - Bani Nurhakim; Rudi Kurniawan; Rifki Hermawan; Muhammad Khoerul Ikhwan (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Community service activities are carried out as an effort to increase the digital competence of Kuningan Regency Vocational School students in facing the development of the modern digital industry. This activity was carried out on May 23 2026 involving participants from several partner schools, namely SMKN 1 Kuningan, SMKN 2 Kuningan, SMK Muhammadiyah Kuningan, SMK Pertiwi Kuningan, and SMK Yamsik Kuningan. Implementation of activities uses a practice-based workshop approach and project-based learning. The training material includes basic concepts of workflow automation, digital system integration, use of the n8n platform, implementation of triggers and actions, as well as development of mini projects based on user needs. Participants gain hands-on experience in building simple workflow automation using Telegram integration, email, Google Sheets, and digital forms. The results of the activity showed an increase in participants' understanding of the concept of workflow automation and the implementation of digital service integration. Participants succeeded in developing various mini projects such as automatic notification systems, automatic email sending workflows, integration of digital forms with spreadsheets, and automation of digital data management. The hands-on practice approach provides a more applicable learning experience and helps improve participants' creativity, problem solving abilities and digital technology skills. Evaluation of activities is carried out through observation, assessment of mini-project results, reflective discussions, and participant satisfaction questionnaires. The evaluation results show that the level of participant satisfaction is in the very good category with a satisfaction percentage of more than 90%. Participants assessed that practice-based training methods and mentoring provide effective learning experiences that are relevant to the needs of the digital industry. In general, this community service activity succeeded in achieving the planned program targets and made a positive contribution to strengthening digital literacy and developing technological innovation in the vocational education environment in Kuningan Regency.